Preparation method of wear-resistant modified nylon plastic
By blending carbon acid chloride nanotubes and diphenylsulfone-based nylon with nylon 6 resin, wear-resistant modified nylon plastic is prepared, which solves the problem of insufficient wear resistance and mechanical properties of nylon 6 materials, and significantly improves the wear resistance and thermal stability of the material.
Patent Information
- Application Number
- CN202510330760.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-20
AI Technical Summary
Nylon 6 material has poor wear resistance and low mechanical properties.
Wear-resistant modified nylon plastics were prepared by blending carbon acid chloride nanotubes and diphenylsulfone-based nylon with nylon 6 resin and melt blending in an extruder.
It significantly improves the tensile strength, elongation of break and bending strength of nylon plastics, reduces the amount of mass wear, improves wear resistance, and enhances thermal stability.
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon, in particular to a method for preparing wear-resistant modified nylon plastic. Background Art
[0002] Nylon 6 is a general-purpose engineering plastic with excellent performance, which is widely used in the fields of automotive parts, electronic appliances, precision equipment and instruments. It is of great significance to improve the mechanical strength, wear resistance and heat resistance of nylon 6 materials. The use of inorganic nanofillers to fill and modify nylon 6 is a research hotspot. Among them, carbon nanotubes are a one-dimensional quantum nanomaterial with a special structure. They have high mechanical strength, strong high temperature resistance, good wear resistance and high thermal conductivity, and are widely used in nylon and other materials.
[0003] Ordinary carbon nanotubes have problems such as poor dispersibility and poor compatibility with nylon 6 resin. The patent with the announcement number CN101746747B discloses that multi-walled carbon nanotubes, styrene and maleic anhydride are subjected to free radical polymerization to obtain styrene maleic anhydride grafted multi-walled carbon nanotubes, which are then added to caprolactam monomer to obtain nylon 6 grafted modified carbon nanotubes, thereby improving the dispersibility of carbon nanotubes and the dispersibility of carbon nanotubes in various polyamides. However, the patent does not improve the wear resistance, heat resistance, mechanical strength and other properties of nylon 6 materials. Summary of the invention
[0004] (1) The present invention solves the problem that nylon plastic has poor wear resistance and low mechanical properties.
[0005] (II) Technical solution: The preparation method of wear-resistant modified nylon plastic is as follows: Step A: The cleaned nylon 6 resin is molded into a film, added to ethanol, and then an initiator and a structure of The grafted monomer is heated to 70-80°C and stirred for grafting reaction for 1-2.5 hours. During the reaction, condensation reflux is added, acetone is added, and the product is filtered and washed with water. The product is extracted with acetone in a Soxhlet extractor and dried to obtain diphenyl sulfone nylon.
[0006] Step B: Add acyl chloride carbon nanotubes to toluene, add diphenylsulfone nylon and triethylamine after stirring, heat to 40-75°C, stir and react for 12-24 hours, concentrate under reduced pressure, wash with water, dry and melt blend the product with nylon 6 resin and antioxidant in an extruder, the temperatures of sections one to six are 230°C, 240°C, 260°C, 270°C, 270°C and 265°C, the screw speed is 100-200r / min, extrude, cool and pelletize to obtain wear-resistant modified nylon plastic.
[0007] Preferably, in step A, the mass concentration of the initiator in the solution is 150-300 g / L, and the concentration of the grafting monomer is 0.4-1.2 g / L. The initiator is dibenzoyl peroxide or azobisisobutyronitrile.
[0008] Preferably, in step B, the masses of the chlorinated carbon nanotubes, diphenylsulfone nylon, and triethylamine are 0.5-6%, 5-30%, and 0.02-0.3% of the mass of nylon 6 resin, respectively.
[0009] Preferably, the preparation method of the grafted monomer is the following steps: Step (1), adding 4-bromomethylbenzyl alcohol, acrylic acid, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide in a molar ratio of 1:(1-1.1):(0.16-0.22):(1.1-1.2) to dichloromethane, stirring the mixture at 20-30°C for 4-7h, concentrating under reduced pressure, separating by silica gel column chromatography, and using ethyl acetate and petroleum ether solution as the eluent to obtain an intermediate.
[0010] Step (2), adding the intermediate, 4-(phenylsulfonyl)aniline and 2,6-lutidine in a molar ratio of 1:(1.2-1.3):(1-1.2) to N,N-dimethylacetamide, stirring the mixture at 50-60° C. for 12-18 hours in a nitrogen atmosphere, concentrating under reduced pressure, separating by silica gel column chromatography, and using ethyl acetate and petroleum ether solution as the eluent to obtain a grafted monomer.
[0011] Preferably, the preparation method of chlorinated carbon nanotubes is: putting carbon nanotubes into concentrated sulfuric acid and concentrated nitric acid for acidification to obtain acidified carbon nanotubes; and then adding them into thionyl chloride and N,N-dimethylformamide for chlorination reaction to obtain chlorinated carbon nanotubes.
[0012] (III) Technical effect of the present invention: The present invention uses 4-bromomethylbenzyl alcohol, acrylic acid and 4-(phenylsulfonyl)aniline as reactants to prepare a graft monomer containing an acrylate structure, and grafts the nylon 6 resin under the action of azobisisobutyronitrile or dibenzoyl peroxide, thereby introducing a diphenyl sulfone polymer containing an active imino group into the nylon 6 material.
[0013] The present invention uses chlorinated carbon nanotubes and diphenyl sulfone nylon as fillers and blends them with nylon 6 resin. The diphenyl sulfone nylon has good compatibility with nylon 6 resin, and the diphenyl sulfone polymer is grafted on the side chain. The diphenyl sulfone polymer contains a heat-resistant benzene ring and a diphenyl sulfone structure. When added to the nylon 6 resin, the thermal stability of the resin plastic can be improved and the thermal decomposition temperature can be increased.
[0014] During the reaction process of the diphenylsulfone nylon of the present invention, the active imino groups react with the acyl chloride groups on the surface of the carbon nanotubes, thereby introducing nylon 6 molecular chains on the surface of the carbon nanotubes, so that the diphenylsulfone nylon can play the role of a compatibilizer, improve the compatibility between the carbon nanotubes and the nylon 6 resin, and the carbon nanotubes are uniformly dispersed in the nylon 6 resin plastic, thereby overcoming the agglomeration problem, having a better reinforcement effect, significantly improving the tensile strength, elongation at break and bending strength of the nylon plastic, reducing the mass wear of the nylon plastic, and improving the wear resistance. Meanwhile, the uniformly dispersed carbon nanotubes can improve the thermal stability of the nylon plastic, so that the nylon plastic has a higher initial thermal decomposition temperature. DETAILED DESCRIPTION
[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0016] Nylon 6 resin, Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd. Carbon nanotubes, Advanced Institute (Shenzhen) Technology Co., Ltd.
[0017] Embodiment 1: (1): 2 g of carbon nanotubes were placed in 180 mL of concentrated sulfuric acid (98% by mass) and 60 mL of concentrated nitric acid (68% by mass), heated to 60 °C, stirred for acidification for 4 h, filtered, washed with water, and dried to obtain acidified carbon nanotubes; then added to 300 mL of thionyl chloride, 3 mL of N,N-dimethylformamide, heated to 70 °C, stirred for reaction for 24 h, filtered, washed with dichloromethane, and dried to obtain acyl chloride carbon nanotubes.
[0018] (2): Add 20 mmol 4-bromomethylbenzyl alcohol, 20 mmol acrylic acid, 3.6 mmol 4-dimethylaminopyridine, and 24 mmol N,N'-dicyclohexylcarbodiimide to 40 mL dichloromethane, stir and react at 25°C for 7 hours, concentrate under reduced pressure, separate by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as eluent to obtain the intermediate. The reaction formula is as follows: .
[0019] (3): Add 20 mmol of the intermediate, 24 mmol of 4-(phenylsulfonyl)aniline, and 22 mmol of the catalyst 2,6-lutidine to 40 mL of N,N-dimethylacetamide, heat to 60°C in a nitrogen atmosphere, stir and react for 12 hours, concentrate under reduced pressure, separate by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as the eluent to obtain the grafted monomer. The reaction formula is: .
[0020] (4): The cleaned nylon 6 resin was molded into a film, added to 100 mL of ethanol, and then 0.04 g of initiator dibenzoyl peroxide and 15 g of grafting monomer were added. The film was heated to 75 °C and stirred for grafting reaction for 1 hour. During the reaction, condensation reflux was added, acetone was added, filtered and washed with water, and the product was extracted with acetone in a Soxhlet extractor and dried to obtain diphenyl sulfone nylon.
[0021] (5): Add 5 g of acyl chloride carbon nanotubes to 150 mL of toluene, stir and then add 50 g of diphenylsulfone nylon and 0.2 g of triethylamine, heat to 60 ° C, stir and react for 12 h, concentrate under reduced pressure, wash with water, dry and then melt blend the product with 1 kg of nylon 6 resin and 4 g of antioxidant 1010 in an extruder. The temperatures of the first to sixth sections are 230 ° C, 240 ° C, 260 ° C, 270 ° C, 270 ° C, 265 ° C, and the screw speed is 200 r / min. Extrude, cool and pelletize to obtain wear-resistant modified nylon plastic.
[0022] Embodiment 2: (1): Add 20 mmol 4-bromomethylbenzyl alcohol, 22 mmol acrylic acid, 4.4 mmol 4-dimethylaminopyridine and 24 mmol N,N'-dicyclohexylcarbodiimide to 50 mL dichloromethane, stir at 30°C for 4 h, concentrate under reduced pressure, separate by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as eluent to obtain the intermediate.
[0023] (2): Add 20 mmol of the intermediate, 26 mmol of 4-(phenylsulfonyl)aniline and 24 mmol of the catalyst 2,6-lutidine to 50 mL of N,N-dimethylacetamide, heat to 60 °C in a nitrogen atmosphere, stir and react for 12 h, concentrate under reduced pressure, separate by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as the eluent to obtain a grafted monomer.
[0024] (3): The cleaned nylon 6 resin was molded into a film and added to 100 mL of ethanol. Then, 0.08 g of initiator dibenzoyl peroxide and 22 g of grafting monomer were added. The film was heated to 70 °C and stirred for grafting reaction for 2.5 h. During the reaction, condensation reflux was added, acetone was added, and the film was filtered and washed with water. The product was extracted with acetone in a Soxhlet extractor and dried to obtain diphenyl sulfone nylon.
[0025] (4): Add 30 g of acyl chloride carbon nanotubes (prepared in the same manner as in Example 1) to 1200 mL of toluene, stir, then add 200 g of diphenylsulfone nylon and 1.5 g of triethylamine, heat to 40 ° C, stir and react for 24 h, concentrate under reduced pressure, wash with water, dry and then melt blend the product with 1 kg of nylon 6 resin and 4 g of antioxidant 1010 in an extruder. The temperatures of the first to sixth sections are 230 ° C, 240 ° C, 260 ° C, 270 ° C, 270 ° C, and 265 ° C. The screw speed is 100 r / min. Extrude, cool, and pelletize to obtain wear-resistant modified nylon plastic.
[0026] Embodiment 3: (1): Add 20 mmol 4-bromomethylbenzyl alcohol, 20 mmol acrylic acid, 3.2 mmol 4-dimethylaminopyridine and 22 mmol N,N'-dicyclohexylcarbodiimide to 40 mL dichloromethane, stir and react at 20°C for 7 h, concentrate under reduced pressure, and separate by silica gel column chromatography with ethyl acetate and petroleum ether solution as the eluent to obtain the intermediate.
[0027] (2): Add 20 mmol of the intermediate, 24 mmol of 4-(phenylsulfonyl)aniline and 20 mmol of the catalyst 2,6-lutidine to 40 mL of N,N-dimethylacetamide, heat to 50 °C in a nitrogen atmosphere, stir and react for 18 h, concentrate under reduced pressure, separate by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as the eluent to obtain a grafted monomer.
[0028] (3): The cleaned nylon 6 resin is molded into a film, added to 100 mL of ethanol, and then 0.12 g of initiator azobisisobutyronitrile and 30 g of grafting monomer are added, heated to 80°C, and stirred for grafting reaction for 2 hours. During the reaction, condensation reflux is added, acetone is added, filtered and washed with water, and the product is extracted with acetone in a Soxhlet extractor and dried to obtain diphenylsulfone nylon.
[0029] (4): Add 60 g of acyl chloride carbon nanotubes (prepared in the same manner as in Example 1) to 2000 mL of toluene, stir, then add 300 g of diphenylsulfone nylon and 3 g of triethylamine, heat to 75 ° C, stir and react for 12 h, concentrate under reduced pressure, wash with water, dry and then melt blend the product with 1 kg of nylon 6 resin and 4 g of antioxidant 1010 in an extruder. The temperatures of the first to sixth sections are 230 ° C, 240 ° C, 260 ° C, 270 ° C, 270 ° C, 265 ° C, and the screw speed is 100 r / min. Extrude, cool and pelletize to obtain wear-resistant modified nylon plastic.
[0030] Comparative Example 1: (1): 1 kg of nylon 6 resin and 4 g of antioxidant 1010 were melt-blended in an extruder. The temperatures of sections 1 to 6 were 230°C, 240°C, 260°C, 270°C, 270°C, and 265°C. The screw speed was 100 r / min. The mixture was extruded, cooled, and pelletized to obtain nylon plastic.
[0031] Comparative Example 2: (1): 5 g of acyl chloride carbon nanotubes (prepared in the same manner as in Example 1), 1 kg of nylon 6 resin, and 4 g of antioxidant 1010 were melt-blended in an extruder. The temperatures of sections 1 to 6 were 230°C, 240°C, 260°C, 270°C, 270°C, and 265°C. The screw speed was 200 r / min. Extrusion, cooling, and pelletizing were performed to obtain wear-resistant modified nylon plastic.
[0032] Comparative Example 3: (1): 50 g of diphenylsulfone nylon (prepared in the same manner as in Example 1), 1 kg of nylon 6 resin, and 4 g of antioxidant 1010 were melt-blended in an extruder. The temperatures of sections 1 to 6 were 230°C, 240°C, 260°C, 270°C, 270°C, and 265°C. The screw speed was 200 r / min. The mixture was extruded, cooled, and pelletized to obtain a wear-resistant modified nylon plastic.
[0033] Comparative Example 4: (1): Add 5 g of carbon nanotubes to 150 mL of toluene, stir, add 50 g of diphenylsulfone nylon (prepared in the same manner as in Example 1) and 0.2 g of triethylamine, heat to 60°C, stir for 12 h, concentrate under reduced pressure, wash with water, dry, and then melt-blend the product with 1 kg of nylon 6 resin and 4 g of antioxidant 1010 in an extruder. The temperatures of the first to sixth stages are 230°C, 240°C, 260°C, 270°C, 270°C, and 265°C. The screw speed is 200 r / min. Extrude, cool, and pelletize to obtain wear-resistant modified nylon plastic.
[0034] Comparative Example 5: (1): Add 5 g of acyl chloride carbon nanotubes (prepared in the same manner as in Example 1) to 150 mL of toluene, stir, then add 50 g of nylon 6 resin and 0.2 g of triethylamine, heat to 60 ° C, stir for 12 h, concentrate under reduced pressure, wash with water, dry, and then melt-blend the product with 1 kg of nylon 6 resin and 4 g of antioxidant 1010 in an extruder. The temperatures of the first to sixth sections are 230 ° C, 240 ° C, 260 ° C, 270 ° C, 270 ° C, and 265 ° C. The screw speed is 200 r / min. Extrude, cool, and pelletize to obtain wear-resistant modified nylon plastic.
[0035] Wear-resistant modified nylon plastic is injection molded into standard specimens through an injection molding machine, and the temperatures of each section of the injection molding machine are 230°C, 245°C, and 240°C.
[0036] The wear resistance is tested according to GB / T 3960-2016. The grinding ring is 45# steel ring, the speed is 200r / min, and the load is 200N.
[0037] The tensile properties are tested according to GB / T 1040.1-2018. The bending properties are tested according to GB / T 9341-2000.
[0038] The thermal stability was tested by a thermogravimetric analyzer in a nitrogen atmosphere, a test temperature of 25-700°C, and a heating rate of 10°C / min.
[0039] Table 1
[0040] Compared with Comparative Example 1, chlorinated carbon nanotubes and diphenyl sulfone nylon are added to the nylon plastics of Examples 1-3. The diphenyl sulfone nylon contains a nylon 6 main chain and has good compatibility with nylon 6 resin, and the side chain is grafted with a diphenyl sulfone polymer, which contains a heat-resistant benzene ring and a diphenyl sulfone structure. When added to the nylon 6 resin, the thermal stability of the resin plastic can be improved and the thermal decomposition temperature can be increased. At the same time, during the reaction process, the active imino groups of diphenylsulfone nylon react with the acyl chloride groups on the surface of the carbon nanotubes, thereby introducing nylon 6 molecular chains on the surface of the carbon nanotubes, so that the diphenylsulfone nylon can play the role of a compatibilizer, improving the compatibility between the carbon nanotubes and the nylon 6 resin. The carbon nanotubes are evenly dispersed in the nylon 6 resin plastic, overcoming the agglomeration problem, and have a better reinforcement effect. The tensile strength, elongation at break and bending strength of the nylon plastic are significantly improved, and the mass wear of the nylon plastic is reduced, and the wear resistance is improved. At the same time, the evenly dispersed carbon nanotubes can improve the thermal stability of the nylon plastic, so that the nylon plastic has a higher starting (mass loss 5%) thermal decomposition temperature.
[0041] In Comparative Example 2, only chlorinated carbon nanotubes are added, which are difficult to react with nylon 6 resin and have poor compatibility with nylon 6 resin. The dispersibility of carbon nanotubes is poor and the reinforcement effect is low. It is difficult to effectively improve the tensile strength, flexural strength and wear resistance of nylon plastic, and the elongation at break of nylon plastic tends to decrease.
[0042] Comparative Example 3 adds diphenyl sulfone nylon, which has good compatibility with the nylon 6 resin matrix and has almost no effect on the mechanical properties of nylon plastic. The mass wear, tensile strength, elongation at break and bending strength are very similar to those of Comparative Example 1. However, the side chains of the diphenyl sulfone nylon are grafted with heat-resistant diphenyl sulfone polymers, which are added to the nylon 6 resin to increase the initial thermal decomposition temperature and heat resistance of the plastic.
[0043] The carbon nanotubes added in Comparative Example 4 do not contain acyl chloride groups and cannot react with diphenylsulfone nylon. Diphenylsulfone nylon cannot act as a compatibilizer and does not improve the compatibility between the carbon nanotubes and nylon 6 resin. The reinforcing effect of the carbon nanotubes is poor, the mass wear is large, and the tensile strength, elongation at break and bending strength are low.
[0044] The nylon 6 resin added in Comparative Example 5 does not contain active imino groups and cannot react with the chlorinated carbon nanotubes. The compatibility between the carbon nanotubes and the nylon 6 resin is not improved. The reinforcing effect of the carbon nanotubes is poor, the mass wear is large, and the tensile strength, elongation at break and bending strength are low.
[0045] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing wear-resistant modified nylon plastic, characterized in that: The preparation method of the wear-resistant modified nylon plastic comprises the following steps: Step A: The cleaned nylon 6 resin is molded into a film, added to ethanol, and then an initiator and a structure of The grafting monomer is stirred to carry out grafting reaction, condensed and refluxed during the reaction, acetone is added after the reaction, filtered and washed, extracted in a Soxhlet extractor, and dried to obtain diphenyl sulfone nylon; Step B: Add acyl chloride carbon nanotubes to toluene, add diphenylsulfone nylon and triethylamine after stirring, concentrate under reduced pressure after stirring for reaction, wash, dry, melt blend the product with nylon 6 resin and antioxidant in an extruder, extrude, cool and pelletize to obtain wear-resistant modified nylon plastic.
2. The method for preparing the wear-resistant modified nylon plastic according to claim 1, characterized in that: In the step A, the mass concentration of the initiator in the solution is 150-300 g / L, and the concentration of the grafting monomer is 0.4-1.2 g / L.
3. The method for preparing the wear-resistant modified nylon plastic according to claim 2, characterized in that: The initiator is dibenzoyl peroxide or azobisisobutyronitrile.
4. The method for preparing the wear-resistant modified nylon plastic according to claim 1, characterized in that: In the step A, the temperature during the grafting reaction is 70-80° C., and the reaction time is 1-2.5 hours.
5. The method for preparing the wear-resistant modified nylon plastic according to claim 1, characterized in that: In the step B, the masses of the chlorinated carbon nanotubes, diphenylsulfone nylon, and triethylamine are 0.5-6%, 5-30%, and 0.02-0.3% of the mass of nylon 6 resin, respectively.
6. The method for preparing the wear-resistant modified nylon plastic according to claim 1, characterized in that: In the step B, the reaction temperature is 40-75° C. and the reaction time is 12-24 h.
7. The method for preparing the wear-resistant modified nylon plastic according to claim 1, characterized in that: In the step B, the temperatures of the extruder sections 1 to 6 are 230° C., 240° C., 260° C., 270° C., 270° C., and 265° C., and the screw speed is 100-200 r / min.
8. The method for preparing the wear-resistant modified nylon plastic according to claim 2, characterized in that: The preparation method of the grafted monomer comprises the following steps: Step (1), adding 4-bromomethylbenzyl alcohol, acrylic acid, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide in a molar ratio of 1:(1-1.1):(0.16-0.22):(1.1-1.2) to dichloromethane, stirring at 20-30° C. for 4-7 hours, concentrating under reduced pressure, and separating by silica gel column chromatography to obtain an intermediate; Step (2), adding the intermediate, 4-(phenylsulfonyl)aniline and 2,6-lutidine in a molar ratio of 1:(1.2-1.3):(1-1.2) to N,N-dimethylacetamide, stirring the mixture at 50-60° C. for 12-18 hours in a nitrogen atmosphere, and concentrating under reduced pressure to obtain a grafted monomer.
9. The method for preparing the wear-resistant modified nylon plastic according to claim 1, characterized in that: The preparation method of the chlorinated carbon nanotubes comprises: placing the carbon nanotubes in concentrated sulfuric acid and concentrated nitric acid for acidification to obtain acidified carbon nanotubes; and then adding the carbon nanotubes into thionyl chloride and N,N-dimethylformamide for chlorination reaction to obtain chlorinated carbon nanotubes.
Citation Information
Patent Citations
Preparation method of nylon-6 grafting modified carbon nano tubes
CN101746747B
High-wear-resistance nylon material
CN117844235A
Spherical particles comprising carbon nanomaterial-graft-polymer and methods of production and uses thereof
US20220389145A1
Cited By
Velvet polishing brush wire and preparation method thereof
CN120590792A